ANALISIS STRUKTUR FISIS DAN SIFAT OPTIK FILM TIPIS SUDAN III HASIL DEPOSISI EVAPORASI VAKUM - Prisilia Wakary; Heinrich Taunaumang; Jimmy Lolowang (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2020)
Thin films based on azobenzene molecular are known as responsive molecular, which are easy to deform when exposed to light or interact whit other molecular. Fabrication of Sudan III thin film for sensor technology application has been carried out bay using PVD method. The physical structure crystallinity of thin film have been investigate by using XRD method. In this paper would be describe the variable distance between the crystal plane, the crystal size, and the crystal index at sudan III in the form of powder and thin film from vacuum evaporation. The optical properties of thin film Sudan III will also be discussed.